INFORMATION TECHNOLOGY'S ROLE IN ENHANCING FINANCIAL REPORT TRANSPARENCY - Hanaa Mathboob; Lec. Nejoom Taher; Zainab Mohammed (Scholars Digest Publishing, 2024)
Hardware, equipment, software, and database are among the significant factors influencing accounting and AIS – related activities in the economic units in general because the information that these tools supply is suitable and quick; thereby contributing to the efficient and timely accomplishment of operations in these units. Besides, the diffusion of IT and its constant evolution day by day has resulted in a continuous and fast pace of changing the technology of collecting, entering, processing, and preparing high-quality financial reports (outputs) which in turn have contributed towards achieving the objective of transparency in the financial reports. Much attention should be paid to the contribution of information technology for enhancing the recognizability of the financial reports. Specifically, to meet the objectives and the hypothesis of the research, 50 questionnaires were recovered from the participants who seemed interested in financial report and information technology. The following conclusions have been made in this study; arguably the most vital conclusion is that information technology being dynamic in its application helps in providing financial report transparent. Other fields of accounting have also undergone integration with information technology in some ways and for instance one of them is the reporting of financial information. The following conclusions were made: It is necessary to conduct training courses for accountants and other employees of accounting and finance departments in economic units with reference to modern educational achievements of the field of information technology, including references to accounting work; Interest in the creation of appropriate conditions for the development of the field of information technology.
Keywords: Information technology, financial reports, transparency of financial reports.